2002
DOI: 10.1128/jcm.40.10.3848-3850.2002
|View full text |Cite|
|
Sign up to set email alerts
|

Reevaluation of Streptococcus bovis Endocarditis Cases from 1975 to 1985 by 16S Ribosomal DNA Sequence Analysis

Abstract: Studies that detected an association between Streptococcus bovis endocarditis and colon carcinoma have not taken into account the recently identified genetic diversity among organisms historically classified as S. bovis. With near full-length 16S ribosomal DNA sequence analysis, organisms cultured from the blood of endocarditis patients at the Mayo Clinic from 1975 to 1985 and previously identified as S. bovis or streptococcus group D nonenterococci were shown to represent S. bovis biotypes I (11 isolates) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Many studies have reported the association of Streptococcus (St.) bovis endocarditis with colon cancer. [1][2][3][4] However, this association has not been investigated. Streptococcus bovis has been divided by biotype into three types, I, II/1, and II/2, although it has recently been reclassifi ed both genetically and biochemically.…”
Section: Introductionmentioning
confidence: 94%
“…Many studies have reported the association of Streptococcus (St.) bovis endocarditis with colon cancer. [1][2][3][4] However, this association has not been investigated. Streptococcus bovis has been divided by biotype into three types, I, II/1, and II/2, although it has recently been reclassifi ed both genetically and biochemically.…”
Section: Introductionmentioning
confidence: 94%
“…[3][4][5][6][7][8][9][10] This bacterium is responsible for a growing number of infective endocarditis (IE) and septicemia cases in elderly and immunocompromised individuals. [11][12][13][14][15][16] Firstly isolated from Koala feces and named for its capacity to degrade host tannins, 17 S. gallolyticus is a common inhabitant of the rumen flora of herbivores. This species has also been found in the gastrointestinal (GI) tract of a wide spectrum of animals, [17][18][19][20][21] including marsupials, mammals and birds.…”
Section: Addendummentioning
confidence: 99%
“…Subsequently, wholemetagenome shotgun sequencing showed that most samples were dominated by Streptococcus infantarius, a species that had been identified previously in other African dairy products (29,30). Of concern, S. infantarius has been linked to several human diseases, including bacteremia (31), endocarditis (32), and colon cancer (33). Aside from S. infantarius, two other potentially pathogenic species, namely, Escherichia coli and Klebsiella pneumoniae, were identified in a subset of samples.…”
Section: Discussionmentioning
confidence: 99%